EXPLORING THE THERAPEUTIC POTENTIAL OF SUNITINIB IN THE MANAGEMENT OF METASTATIC ALVEOLAR SOFT PART SARCOMA: A COMPREHENSIVE CASE REPORT - Ali, Insia; Dawood, Tasneem; Khan, Saqib Raza; Minhas, Khurram; Rashid, Yasmin Abdul; Moosajee, Munira (Journal of Ayub Medical College Abbottabad, 2025)
Background: Alveolar soft part sarcoma is a rare subtype of sarcoma. It comprises around 0.5% of all soft tissue sarcomas. It is a disease of the young, mainly affecting people less than 25 years of age. Its incidence is much higher in females than in males. In some instances, it may be associated with exposure to prior radiation and genetic syndromes such as Li Fraumeni and Retinoblastoma. It is a very slow-growing tumour. It can metastasize to the lungs, bones, or brain. It has an overall survival rate of around 56%. Case Report: We report the case of a 22-year-old female patient. She is a known case of Metastatic retroperitoneal Alveolar soft part sarcoma with lung metastasis. She was initially evaluated outside our institute for complaints of abdominal pain and a large left retroperitoneal mass, measuring 17×9×13.5 cm, extending to the left pelvis. She had a locally unresectable disease. CT scan of the Chest revealed bilateral sub-centimeter pulmonary nodules, approximately 8.6 mm in diameter. She later came to us for further management. She had complaints of abdominal pain and discomfort. Following a thorough discussion, she was counselled about the diagnosis of metastatic disease, and it was explained that the treatment would be palliative in intent. She was started on treatment with Sunitinib 37.5 mg once a day. She was also assessed for genetic syndromes. Her genetic test was negative. She has been tolerating the treatment well. Conclusion: This tumour is very rare, and data are scarce regarding its presentation and management. There is no consensus on the treatment of this disease yet, and it follows an indolent course with an increased risk of distant metastases. Targeted treatment, including novel small tyrosine kinase inhibitors in patients with metastatic disease, has shown some promising results regarding response to these therapeutically resilient soft tissue sarcomas along with improved survival.